2016
DOI: 10.18203/2319-2003.ijbcp20164098
|View full text |Cite
|
Sign up to set email alerts
|

Prospective observational study to evaluate the pattern of adverse drug events in cancer patients receiving anti-cancer agents in a tertiary care hospital

Abstract: Background: Adverse drug reactions (ADRs) associated with the use of anticancer drugs are a worldwide problem and cannot be overlooked. They range from nausea, vomiting or any other mild reaction to severe myelosuppression. The study was planned to evaluate the pattern of adverse drug events to anti-cancer agents in a tertiary care hospital. Methods: This observational prospective study was carried out in a tertiary care hospital from 1st January 2011 to 31st December 2011. A total of 213 patients who fulfille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Regarding causality, most ADRs were classified as possible with a low percentage of certain cases. This finding is similar to a study conducted by Joshi et al which showed that the causality of most ADRs was possible with no certain ADRs [27] . Different results were found in other studies carried out in South India [28] .…”
Section: Discussionsupporting
confidence: 92%
“…Regarding causality, most ADRs were classified as possible with a low percentage of certain cases. This finding is similar to a study conducted by Joshi et al which showed that the causality of most ADRs was possible with no certain ADRs [27] . Different results were found in other studies carried out in South India [28] .…”
Section: Discussionsupporting
confidence: 92%